The grotesque at Panel 32 of Atlas Mnemosyne (Palíndromo, 2023)
The category of grotesque is addressed through the analysis of panel 32 of Atlas Mnemosyne by Aby Warburg. The panel contains mainly Renaissance images, approaching themes that span the ages since Antiquity, such as the dance of the moresca, the amorous courtship and the cult of the goddess Venus, the pictorial genre of Singeries (monkeys) and the battle for the trousers. A panel solely dedicate to the grotesque affirms the vigor of this aesthetic category. Together with the analysis of the images, we presente definitions and reflections on the grotesque as approached by André Chastel, Wolfgang Kayser, and, mainly in Victor Hugo. For the French wiriter, the grotesque form is opposed to the classic and exists in nature and not world around us, even if in a kaleidoscope of (in)definitions. Other aesthetic categories are approached in parallel, such as the beauty, for which the grotesque appears as a contrast; the comic; the ugly, with its contrasting diversity to the unity of beauty. The images selected by Warburg pervade such theoretical reflections and reveal fundamental polarities to understand the expression of human commotions: Dionysian-Apollinae, madness-reason, animal-human, liberation-domestication, chaos-order, pathos-logos, distancing-immersion, energetic expansion – energy containment. This article also tries to understand a method in Aby Warburg, whether in the selection and organization of images on the panel; it shows Warburg thematic interests, in this case, festivals and popular traditions; and also, his interest in the dissonant, beyond reductionist generalizations and art history's canonical objects.
Keywords: Atlas Mnemosyne; Aby Warburg; Panel 32 of Atlas Mnemosyne; grotesque